2011
DOI: 10.1148/radiol.11100978
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Monochromatic Spectral Imaging with Fast Kilovoltage Switching: Improved Image Quality as Compared with That Obtained with Conventional 120-kVp CT

Abstract: VMS imaging at approximately 70 keV yielded lower image noise and higher CNR than did 120-kVp CT for a given radiation dose. VMS imaging has the potential to replace 120-kVp CT as the standard CT imaging modality, since optimal VMS imaging may be expected to yield improved image quality in a patient with standard body habitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
246
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(266 citation statements)
references
References 15 publications
16
246
1
3
Order By: Relevance
“…They concluded that 70-keV virtual monoE images had lower noise and higher CNR in comparison to conventional 120-kVp images [15]. Although they used phantoms and our study is a prospective study on patients, our results are consistent.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…They concluded that 70-keV virtual monoE images had lower noise and higher CNR in comparison to conventional 120-kVp images [15]. Although they used phantoms and our study is a prospective study on patients, our results are consistent.…”
Section: Discussionsupporting
confidence: 82%
“…Matsumoto et al compared the image quality of virtual monoE images from fast kilovoltage switching to conventional 120-kVp in phantoms [15]. They concluded that 70-keV virtual monoE images had lower noise and higher CNR in comparison to conventional 120-kVp images [15].…”
Section: Discussionmentioning
confidence: 99%
“…Because CNR is calculated as contrast divided by image noise, the low image noise of the monochromatic images may be another factor that contributes to the higher CNR. Previous studies have also shown that the image noise on monochromatic images was lowest at approximately 70 keV within the range 40-140 keV [13] and lower than that of conventional 120 kVp CT [10]. This indicates that the monochromatic mode can yield higher quality images than the polychromatic mode, not only from increasing contrast but also from decreasing noise.…”
Section: Discussionmentioning
confidence: 81%
“…The reconstruction thickness was 5 mm, at intervals of 5 mm. The data acquired in the spectral CT imaging mode were used to produce one set of conventional polychromatic images and one set of monochromatic images (70 keV) [10]. The polychromatic images were reconstructed using a standard CT reconstruction algorithm.…”
Section: Imaging Techniquementioning
confidence: 99%
“…Virtual monochromatic images (VMI) (65) are obtained applying attenuation measurements in two basic materials such as iodine and water, which are transformed into densities obtained from low and high voltage peak projections and then rebuilt to originate the base material image pairs. Monochromatic examination allows the visualization of the tissues at different energy levels ranging from 40 to 140 keV (Siemens and GE) and up to 200 keV (Philips).…”
Section: Monochromatic Examinationmentioning
confidence: 99%